2018
DOI: 10.21037/jtd.2018.09.100
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced recovery after surgery program for video-assisted thoracoscopic surgery anatomical lung resections is cost-effective

Abstract: Background: Enhanced recovery after surgery (ERAS) programs have been reported to decrease complications and shorten hospital stays after lung resections, but their implementation requires time and financial investment with dedicated staff. The aim of this study was to evaluate the clinical and economic outcomes of video-assisted thoracoscopic surgery (VATS) anatomical pulmonary resections before and after implementation of an ERAS program. Methods: The first 50 consecutive patients undergoing VATS lobectomy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 21 publications
(33 reference statements)
4
41
0
Order By: Relevance
“…Similar to our findings, Gerardi et al observed a reduction of hospital costs by $5'410 per patient [20]. Furthermore, the results of the present study are in line with findings in colorectal, hepato-biliary, thoracic or earnose-throat (ENT) surgeries [7,14,[21][22][23]. In these areas ERAS pathways proved to be cost-beneficial, partly due to decreased complications.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, Gerardi et al observed a reduction of hospital costs by $5'410 per patient [20]. Furthermore, the results of the present study are in line with findings in colorectal, hepato-biliary, thoracic or earnose-throat (ENT) surgeries [7,14,[21][22][23]. In these areas ERAS pathways proved to be cost-beneficial, partly due to decreased complications.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the older patients had poor pulmonary function performance as compared to their counterparts, which indicated that the postoperative risk complications were higher with older patients (≥ 70 years of age) as compared to younger patients (≤ 70 years of age). The ERAS model was rst proposed by the Danish surgeon Kehlet in 1997 [39][40][41]. It refers to the comprehensive use of a series of optimization measures supported by evidence-based medicine during the perioperative period, including multidisciplinary collaboration of surgery, anesthesia, nursing, and nutrition, to optimize the clinical pathway for perioperative management, in order to reduce the perioperative stress response (i.e., physiological and psychological traumatic stress) and postoperative complications in surgical patients with the aim of achieving the best health status and rapid recovery with minimal cost.…”
Section: Discussionmentioning
confidence: 99%
“…It refers to the comprehensive use of a series of optimization measures supported by evidence-based medicine during the perioperative period, including multidisciplinary collaboration of surgery, anesthesia, nursing, and nutrition, to optimize the clinical pathway for perioperative management, in order to reduce the perioperative stress response (i.e., physiological and psychological traumatic stress) and postoperative complications in surgical patients with the aim of achieving the best health status and rapid recovery with minimal cost. Since the ERAS model was successfully applied for the rst time in gastrointestinal surgery, this concept has now been adopted in neurosurgery, thoracic surgery, and other surgical elds [39][40][41]. Studies have shown that under the ERAS protocol, it is possible to effectively reduce surgical trauma and postoperative stress response, shorten the length of hospitalization, and promote patient recovery in the perioperative period of VATS lobectomy [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations